0287 Effects of Sleep Restriction and Recovery on the Capacity of Glucocorticoids to Inhibit Inflammatory Marker Expression in Human Monocytes. (25th May 2022) - Engert, Larissa; Eske, Annika; Buraks, Olivia; Dang, Rammy; Mullington, Janet; Haack, Monika
Abstract: Introduction: Chronic low-grade systemic inflammation is involved in the pathogenesis of many human diseases. Common sleep patterns of restricting sleep during weekdays and catching up on sleep over the weekend induce inflammatory upregulation that may not resolve following weekend recovery sleep. We hypothesize that this sleep pattern leads to an inflammatory imbalance of markers regulating inflammatory homeostasis, including inflammatory markers (eg, interleukin-6 (IL-6) and cyclooxygenase 2 (COX-2)) and markers of counter-inflammation (eg, glucocorticoids (GCs)). The enzyme COX-2 is involved in prostaglandin synthesis and is the target of pain-relieving nonsteroidal anti-inflammatory drugs (NSAIDs). GCs are used in the treatment of many inflammatory diseases, including severe acute infection with SARS-CoV-2. We investigated if sleep restriction impairs the capacity of GCs to inhibit inflammatory COX-2 expression in a preliminary dataset. Methods: The present preliminary dataset (N=6, 2F/4M) derives from an ongoing randomized controlled within-subjects trial consisting of three 11-day in-hospital protocols (2 restricted sleep arms, 1 control sleep arm). The ongoing study is blinded for administration of placebo or aspirin under sleep restriction. Under restricted sleep conditions, 2 nights of baseline sleep (8h/night) were followed by 5 nights of restricted sleep (4h/night), concluding with 3 nights of recovery sleep (8h/night). In the control condition, participants could sleep 8h/night throughout the entire protocol. Blood samples were taken after baseline sleep, after 5 nights of restricted or control sleep, and after 2 nights of recovery sleep. Data were analyzed using generalized linear mixed models. Results: Sleep restriction was associated with decreased capacity of GCs to inhibit COX-2 expression in monocytes (p<.01) and has the expected inflammatory effect on IL-6 production in monocytes (p<.01). Moreover, sleep restriction has lasting inflammatory effects as shown in increased inflammation following 2 nights of recovery sleep (p<.01). Conclusion: In conclusion, the present preliminary analysis suggests that in patients treated with GCs, sleep restriction potentially reduces their effectiveness in controlling inflammation, thus contributing to increased inflammation-related morbidity. Sample collection and data analysis is ongoing. Support (If Any): NIH/NHLBI R01-HL136310; NIH/NCRR UL1-RR02758, M01-RR01032; German Research Foundation (DFG) EN1291/1-1.